An Analysis of the Enola Holmes 2 Movie From A Perspective of Feminist Theory - Dika Putra Pamungkas; Abdillah Nugroho (Universitas Cokroaminoto Palopo, 2023)
This research took the ''Enola Holmes 2'' movie as the object of research regarding the analysis of feminism contained in the movie. Feminism is still a very important issue for women to voice gender equality and rights with men. This research aims to find out the characteristics of the main character Enola Holmes and find out how the main character reflected feminism. The method used in this research is qualitative research method to solve the problem formulation in ''Enola Holmes 2'' movie. The data taken for this research is in the form of transcripts of conversations in the ''movie Enola Holmes 2''. In addition to being unlike other women at the time, Enola exhibits traits like bravery and tenacity in the movie. She also has dreams of becoming a detective, which is something that few women do. Enola, who was undervalued due to her ambition and undervalued due to her gender, was able to realize her aspirations and rose to fame as a well-known female detective. The movie ''Enola Holmes 2'' proves that feminism is not just about seeking the right to gender equality but also about the value of supporting fellow women and protecting other women.